ADVOCACY VERSUS ENFORCEMENT IN ANTITRUST COMPLIANCE PROGRAMS. (21st March 2020) - Chang, Hung Hao; Sokol, D Daniel
Abstract: We focus on the question of why firms self-regulate to avoid more severe public regulation in the area of antitrust compliance. We distinguish the effects of an antitrust authority's outreach and enforcement on firms' adoption of antitrust compliance programs. Furthermore, we examine the mechanism that may drive an antitrust authority's actions on firms' decisions to adopt compliance programs. Using a 2-year survey of 432 firms drawn from the top 300 Taiwanese enterprises and applying mediation analysis, we find that "voluntary" self-regulation actions, encouraged by the antitrust authority to promote compliance programs through advocacy, significantly increase the creation of antitrust compliance programs. Moreover, "coercive" actions of the antitrust authority in terms of enforcement are less effective than voluntary actions for firms' compliance program creation. Within "coercive" actions, large fines are more likely to lead to the adoption of antitrust compliance programs relative to other forms of government prosecution.